Highly efficient removal of cationic, anionic and neutral dyes by hierarchically porous structured three-dimensional magnetic sulfur/nitrogen co-doped reduced graphene oxide nanohybrid. (October 2020) - Rong, Yanqin; Huang, Yu; Jin, Pengyue; Yang, Cheng; Zhong, Zhihui; Dong, Chuan; Liang, Wenting
Graphical abstract: Abstract: The versatile three-dimensional magnetic sulfur/nitrogen co-doped reduced graphene oxide nanomaterials (3D-MSNGs) have been constructed and generated via interfacial coordination assembly of three-dimensional sulfur/nitrogen dual-doped reduced graphene oxide (3D-SNG) with concurrent modification by formed magnetic Fe3 O4 . Using ferric ions as iron source, the as-obtained nanohybrid 3D-MSNG-1 possesses abundant hierarchical porous structure on graphene network, large BET surface area and favorable magnetic properties, which is proved excellent adsorption capacity and easy magnetic separation. When 3D-MSNG-1 was utilized to absorb the dyes of methylene blue (MB), congo red (CR) and neutral red (NR) considered as cationic, anionic and neutral model dye molecules, respectively, the adsorption equilibrium for MB, CR and NR were rapidly achieved in 15 min. The adsorption isotherm fits Langmuir adsorption model well with the maximum uptake capacity for MB, CR and NR high to 171.53 mg/g, 909.09 mg/g and 877.19 mg/g, respectively. Meanwhile, an efficacious treatment of ternary dyes mixed solution and a good recyclability manifests that 3D-MSNG-1 is supposed to be a superior adsorbent in the areas of water treatment.